Control of a grinding mill circuit using fractional order controllers. (May 2017) - Aguila-Camacho, Norelys; Le Roux, Johan D.; Duarte-Mermoud, Manuel A.; Orchard, Marcos E.
Abstract : Highlights: Control of a grinding mill circuit using fractional order SISO controllers is addressed. A continuous time dynamic phenomenological non-linear population balance model is used to describe and simulate the circuit. Designed controllers can achieve similar or better results to that achieved using linear model predictive control, which is an advanced multivariable control techniques. Controllers are tested in the presence of disturbances and process noise. Abstract: This paper presents the design and application of fractional single-input–single-output (SISO) controllers to a grinding mill circuit, which is a multiple-input–multiple-output (MIMO) process. Two kinds of controllers are presented: fractional order proportional-integral (FOPI) controllers, and a combination of FOPI and fractional order model reference adaptive controllers (FOMRAC). The parameters of the controller are tuned using off-line particle swarm optimization. In the presence of disturbances and process noise, the SISO fractional controllers achieve similar or better performance compared to linear model predictive control (LMPC).